2014
DOI: 10.3727/096368914x678454
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine (PolyQ) Diseases: Genetics to Treatments

Abstract: The polyglutamine (polyQ) diseases are a group of neurodegenerative disorders caused by expanded cytosineadenine-guanine (CAG) repeats encoding a long polyQ tract in the respective proteins. To date, a total of nine polyQ disorders have been described: six spinocerebellar ataxias (SCA) types 1, 2, 6, 7, 17; Machado-Joseph disease (MJD/SCA3); Huntington's disease (HD); dentatorubral pallidoluysian atrophy (DRPLA); and spinal and bulbar muscular atrophy, X-linked 1 (SMAX1/SBMA). PolyQ diseases are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
138
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 234 publications
(248 reference statements)
0
138
0
2
Order By: Relevance
“…Compared to normal tau, genetic mutation in or post-translational modification of tau facilitates the formation of tau aggregates. Similar intracellular protein oligomer and aggregate conformers found in other neurodegenerative diseases, such as mutant Huntingtin in Huntington's disease [9,10], Spinocerebellar ataxia type 1 (SCA) in spinocerebellar ataxia [11], alpha-synuclein in Parkinson's disease [12], and TAR DNAbinding protein-43 (TDP-43) in amyotrophic lateral sclerosis [13] are also thought to induce the respective diseases [14]. Therefore, it is important to study the tau species between oligomers and aggregates found in Alzheimer's disease, with particular attention to their role in memory impairment and the loss of synaptic function.…”
Section: Introductionmentioning
confidence: 93%
“…Compared to normal tau, genetic mutation in or post-translational modification of tau facilitates the formation of tau aggregates. Similar intracellular protein oligomer and aggregate conformers found in other neurodegenerative diseases, such as mutant Huntingtin in Huntington's disease [9,10], Spinocerebellar ataxia type 1 (SCA) in spinocerebellar ataxia [11], alpha-synuclein in Parkinson's disease [12], and TAR DNAbinding protein-43 (TDP-43) in amyotrophic lateral sclerosis [13] are also thought to induce the respective diseases [14]. Therefore, it is important to study the tau species between oligomers and aggregates found in Alzheimer's disease, with particular attention to their role in memory impairment and the loss of synaptic function.…”
Section: Introductionmentioning
confidence: 93%
“…Although genetic studies have elucidated the function of Ago2 in D. melanogaster, the role of the GRR is still unknown. In other proteins, long polyglutamine-rich regions have been implicated in increased protein adhesion and protein complex formation, and underlie numerous human diseases (reviewed in Fan et al 2014). However these are generally long contiguous tracts of glutamine residues, in contrast to the short complex repeat units observed in the Ago2 GRR.…”
mentioning
confidence: 95%
“…There is much debate as to the exact role neuronal nuclear inclusions plays in pathogenesis, as researchers are still unable to determine whether the aggregates directly induce neurodegeneration or if the presence of misfolded proteins and oligomeric intermediates are to blame [7,8,[222][223][224]. However, the prevention or reversal of neuronal nuclear inclusions still remains one of the most attractive avenues for therapeutic treatment [225].…”
Section: Prevention Of Misfolding and Protein Aggregationmentioning
confidence: 99%
“…These six diseases (SCA1, 2,3,6,7,17) are caused by an expansion of a CAG repeating sequencing in the coding region of six independent genes. All six diseases present with common ataxic symptoms, however, there is still a large degree of phenotypic variation, from the rapid and early progression of SCA7, to the more slowly progressive, milder form of SCA6.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation